Effect of Clinacanthus nutans leaf extract on oral mucosal burns and tongue wounds: An in-vivo study - Moehamad Orliando Roeslan; Salsabila Hany Reskia; Fathin Raihanah Firman; Hastania Sakti Dewa; Komariah Komariah; Del Afriadi Bustami (Wolters Kluwer Medknow Publications, 2021)
Background: Clinacanthus nutans exhibits antioxidant, anti-inflammatory, antiviral, anticancer, and anti-biofilm activities. Wounds in the oral cavity can affect the quality of life. Wound healing is a complex process to restore functions of injured tissues. The effect of C. nutans on oral mucosal burns and tongue wounds of rats is investigated. Methods: Forty male Sprague Dawley rats were divided into negative control and treatment groups with 25, 50, and 100 mg/mL of C. nutans. Oral mucosal burns and tongue wounds were observed on days 7 and 14 based on the fibroblast count and collagen deposits. Data were analyzed by analysis of variance and post hoc Tukey's test with P < 0.05. Results: Results revealed that on day 7, the fibroblast count of mucosal burns and tongue wounds increases. The maximum mucosal burns were observed for the 100 mg/mL group, whereas the maximum tongue wounds were observed for the 25 mg/mL group. On day 7, collagen deposits were increased in case of mucosal burns. The number of collagen deposits increased on day 14, the highest mucosal burns were observed for the 100 mg/mL group, and in case of tongue wounds, the highest number was observed for the 50 mg/mL group. Conclusion: Ethanol extracts of C. nutans leaves can increase the fibroblast count on day 7 and collagen deposits on day 14 after injury in case of oral mucosal burns and tongue wounds during the wound healing of Sprague Dawley rats.